2005
DOI: 10.1039/b503897a
|View full text |Cite
|
Sign up to set email alerts
|

Thio arsenosugars in freshwater mussels from the Danube in Hungary

Abstract: In contrast to the large body of data on naturally-occurring arsenic compounds in marine organisms, relatively little is known about arsenic speciation in freshwater biota. We report an investigation using HPLC-ICPMS into the arsenic compounds in five species of freshwater mussels collected from five sites from the Danube in Hungary. Total arsenic concentrations in the mussels ranged from 3.8-12.8 mg As kg(-1). The arsenic speciation patterns were broadly similar for mussels representing each of the five speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
2
26
0
2
Order By: Relevance
“…Thus, in some samples, the sum of the individual As species levels was less than the total As level measured, because the unknown forms of As were not quantified. In addition to the measured As forms reported here, there are as many as 18 other forms that have been identified in environmental and biological systems (Francesconi et al 1999; Le et al 1999, 2004; Miguens-Rodriguez et al 2002; Montilla et al, unpublished data; Sanchez-Rodas et al 2002; Schmeisser et al 2004; Soeroes et al 2005). These forms include dimethylarsinoylethanol, several arsenosugars, and thioarsenosugars found in shrimp, oysters, and seaweed.…”
Section: Resultsmentioning
confidence: 57%
“…Thus, in some samples, the sum of the individual As species levels was less than the total As level measured, because the unknown forms of As were not quantified. In addition to the measured As forms reported here, there are as many as 18 other forms that have been identified in environmental and biological systems (Francesconi et al 1999; Le et al 1999, 2004; Miguens-Rodriguez et al 2002; Montilla et al, unpublished data; Sanchez-Rodas et al 2002; Schmeisser et al 2004; Soeroes et al 2005). These forms include dimethylarsinoylethanol, several arsenosugars, and thioarsenosugars found in shrimp, oysters, and seaweed.…”
Section: Resultsmentioning
confidence: 57%
“…The stability of (oxo-) arsenosugar compounds in a comparable acidic environment (0.078 M HCl) has previously been systematically investigated by Gamble et al [29], and no degradation to inorganic arsenic was observed. The same accounts for the thio-arsenosugars, which presence have been reported in algae and bivalves [30], since they will convert to their oxo-analogues when exposed to an oxidising environment [31] like the presence of the strong oxidant H 2 O 2 in the extractant solution, and hence not be present in the extracts. Additionally, no significant change in the iAs levels during extraction of real samples was found, since the HPLC-ICP-MS analysis of extracts gave~100% recovery for the marine samples spiked with iAs (unpublished data).…”
Section: Extractionmentioning
confidence: 74%
“…There have also been several reports of arsenobetaine in freshwater organisms (Slejkovec et al, 2004;Schaeffer et al, 2006), although the levels are generally low (<0.1 mg arsenic/kg dry mass), much lower than those found in marine samples. Farmed freshwater fish (aquaculture products) can contain arsenobetaine at higher concentrations because they are provided with feed containing marine ingredients (Soeroes et al, 2005). The reason for the observed differences in arsenobetaine content between marine and freshwater organisms is still not known although cumulative evidence suggests that it is related to salinity and that arsenobetaine may be serving as an adventitiously acquired osmolyte (Larsen and Francesconi, 2003;Clowes and Francesconi, 2004).…”
Section: Arsenobetainementioning
confidence: 99%